Alcohol Free - Kotis, Nikoletta (Kotis, Nikoletta, 2008)
Verzio FF Submission The protagonists of this documentary are all men around the age of 60 and 70 who in an earlier stage of their lives had become addicted to alcohol. “Alcohol Free” illustrates the world of these former alcoholics. They have found a way out with the help of the people running anti-alcoholism gatherings in several centers in Hungary. Now, they talk freely, although not indifferently, about their former lives, their reasons for drinking, and the effects that it had on themselves and their families.